“NOI ITALIANI SIAMO COSÌ”: REALIZZARE L’IDENTITÀ IN UNA CONVERSAZIONE DI EMIGRATI ITALIANI (ItalianoLinguadue, 2023)
Una delle questioni principali nel campo della linguistica migrazionale è senza dubbio la costruzione dell’identità intesa come la costruzione linguistica dell’appartenenza ad uno o più gruppi sociali o categorie, costruita attraverso determinate pratiche linguistiche. La nozione d’identità è considerata un costrutto flessibile: la stessa persona può mettere in scena identità multiple in dipendenza dai diversi contesti d’interazione. La presente ricerca si concentra sul modo in cui le identità sono costruite e in particolare sulle strategie usate dai parlanti per rappresentare le proprie identità. I dati sono tratti dalle conversazioni di sette emigranti calabresi e mostrano come gli informanti indessicalizzano la loro identità come appartenente alla propria cultura o alla cultura del paese d’arrivo. “Noi italiani siamo così”: realising identity in Italian migrants’ conversations  One of the main issues in the field of migration linguistics is the construction of identity within discursive practices where speakers call their identities into question starting from the language.  Indeed, identity is intended as the linguistic construction of the membership to one or more social groups or categories that are constructed through the use of communicative practices. We assume the notion of identity as a flexible construct: the same person can enact multiple identities depending on the different contexts of interaction. Our study focuses on the way identities are built and used in an encounter and, in particular, on the following research questions: Which strategies do speakers use to represent their identity? Which kind of identity do they perform? Data are taken from the conversations of seven Calabrian emigrants. Our data show that informants alternatively classify themselves as part of their own culture or the culture of the host country, through the stories they tell, showing a plurality of emerging and conflictual identities.